Fatty acid diversity and interrelationships in macadamia nuts. (15th January 2022) - Hu, Wei; Fitzgerald, Melissa; Topp, Bruce; Alam, Mobashwer; O'Hare, Tim J.
Abstract: Macadamia nuts are an abundant source of monounsaturated fats which exhibit beneficial biological functions and reduce the risk of chronic disease. This study focuses on investigating the fatty acid profile of 197 diverse accessions of macadamia, across cultivars, wild accessions, and three Macadamia species. Macadamia accessions with potential enhanced nutritional value were identified, with eight promising lines detected. The interrelationship of C16:0, C18:0, C18:1, trans -C18:1 fatty acids was determined, and two possible biosynthetic pathways proposed: (1) a previously unidentified C16:0 desaturase is responsible for the desaturation of C16:0 and C18:0 desaturase is responsible for the desaturation of C18:0, with the former being less efficient, and: (2) C18:0 desaturase is responsible for desaturation of both C16:0 and C18:0, but shows weaker specificity towards C16:0. Further, timing of upregulation of C16:0 elongase during kernel development could further modify the fatty acid profile, by reducing the amount of C16:0 substrate available for desaturation. Highlights: The investigation of the fatty acid profile of 197 diverse accessions of macadamia. Finding macadamia varieties with potential nutrition and commercial value. The identification of the interrelationship of the main fatty acids in macadamia. The proposal of two possible biosynthetic pathways of the main fatty acids. Comparison of the fatty acid profile between different macadamia varieties.